2014
DOI: 10.1136/bcr-2013-202784
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya disease, revascularisation surgery and anaesthetic considerations

Abstract: We report a case of a rare disease that requires a unique anaesthetic approach for a unique surgical procedure. Anaesthesiologists need to be familiar with different pathophysiological aspects of this disease and its perioperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Similarly, a study noted that MMD has a bimodal age distribution with one peak in the first decade of life and the other in the fourth decade of life. [ 5 ] A previous study indicated that patient age was a significant factor to predict postoperative symptomatic hyperperfusion in patients with MMD. [ 8 ] In contrast to the previous report, this study showed that patient age was not associated with postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study noted that MMD has a bimodal age distribution with one peak in the first decade of life and the other in the fourth decade of life. [ 5 ] A previous study indicated that patient age was a significant factor to predict postoperative symptomatic hyperperfusion in patients with MMD. [ 8 ] In contrast to the previous report, this study showed that patient age was not associated with postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 4 ] The clinical presentation of MMD mainly includes ischemic stroke, transient ischemic attack, headache, and seizure. [ 5 , 6 ] No medicines, such as antiaggregants, antiepileptics, or vasodilators, are proven to cure or reverse the progression of MMD. [ 6 ] Medicines for MMD only aim to reduce the impact of the symptoms and the risk of thrombosis and sustain normotension.…”
Section: Introductionmentioning
confidence: 99%
“…It is either direct, in which the superficial temporal artery branch of the external carotid artery is directly anastomosed with the middle cerebral artery, or indirect as in synangiosis procedures, where muscle or dura are placed in contact with the surface of the ischaemic brain. Indications for revascularization surgery include ischaemic symptoms or underperfused hemispheres [50]. Secondary stroke prevention using antiplatelets is recommended.…”
Section: Moyamoya Angiopathymentioning
confidence: 99%
“…17,18 The use of propofol may suppress cerebral metabolism and cause a decrease in cerebral blood flow. 19,20 The cerebral effects of opioids that may result in a modest reduction in the cerebral metabolic rate and intracranial pressure depend on systemic hemodynamics, concomitant use of other anesthetic agents, and underlying comorbidities. However, opioids are potent analgesics and are beneficial in stabilizing patient hemodynamics.…”
Section: Discussionmentioning
confidence: 99%